Unes cançons amoroses inèdites de la primera meitat del segle XVI. Estudi i edició - Garau Amengual, Jaume (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: A philological edition and literary study of 22 anonymous love songs found in an accounting manuscript in the Chapter Archive of Mallorca.